การเตรียมเส้นใยพอลิอะคริโลไนไตรล์เพื่อเป็นตัวดูดซับในการสกัดด้วยวัฏภาคของแข็งสำหรับการ วิเคราะห์ปริมาณ PAHs ในน้ำ - พิมลทิพ ชยันต์ตระกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
In this work, polyacrylonitrile fibers were fabricated by electrospinning technique and used as a sorbent in solid phase extraction for determination of polycyclic aromatic hydrocarbons (PAHs). The optimized condition for preparing electrospun polyacrylonitrile fibers were 3 mL of 10% polyacrylonitrile, flow rate of 8 L/min, high voltage of 22 kV and distance between needle and collector of 10 cm. Then, electrospun polyacrylonitrile fibers were characterized by scanning electron microscopy (SEM). The polyacrylonitrile fibers were smooth, uniform and no bead. The average diameter of fibers was 834.5 nm. Next, the prepared fibers were examined for extracting PAHs in water. From the study, the best elution solvent was 1 mL of hexane. %Recovery of spiked water with 7 PAHs at 50 μg/L ranged from 8 to 50.2% with the relative standard deviation (RSD) less than 5%.